2017
DOI: 10.1126/science.aaf7497
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based protein profiling reveals off-target proteins of the FAAH inhibitor BIA 10-2474

Abstract: A recent phase 1 trial of the fatty acid amide hydrolase (FAAH) inhibitor BIA 10-2474 led to the death of one volunteer and produced mild-to-severe neurological symptoms in four others. Although the cause of the clinical neurotoxicity is unknown, it has been postulated, given the clinical safety profile of other tested FAAH inhibitors, that off-target activities of BIA 10-2474 may have played a role. Here, we use activity-based proteomic methods to determine the protein interaction landscape of BIA 10-2474 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
224
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(235 citation statements)
references
References 39 publications
5
224
0
Order By: Relevance
“…However, the nature of this off‐target effect remains obscure, although much speculation has centered around the idea that 8 l is not particularly selective for FAAH. In fact, a recent activity‐based profiling of serine hydrolases revealed that 8 l inhibited not only FAAH, but ABHD6 and some other serine hydrolases, namely FAAH2, CES1, CES2, CES3, ABHD11, LIPE, and PNPLA6, albeit at concentrations several‐fold higher than those needed for FAAH inhibition . Although the published data provide information about the selectivity of 8 l , they do not allow a conclusion about which of the identified off‐targets could be responsible for the observed toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…However, the nature of this off‐target effect remains obscure, although much speculation has centered around the idea that 8 l is not particularly selective for FAAH. In fact, a recent activity‐based profiling of serine hydrolases revealed that 8 l inhibited not only FAAH, but ABHD6 and some other serine hydrolases, namely FAAH2, CES1, CES2, CES3, ABHD11, LIPE, and PNPLA6, albeit at concentrations several‐fold higher than those needed for FAAH inhibition . Although the published data provide information about the selectivity of 8 l , they do not allow a conclusion about which of the identified off‐targets could be responsible for the observed toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…[6] This is because this class of chemical matter can also perform many frontier functions that have been minimally utilized to date. These include modulating protein-protein interactions, [7] allosterically modifying protein function, [8] acting as prostheses on the molecular scale, [9] serving as next-generation biological probes, [10] enabling miniaturized diagnostics, [11] harvesting sunlight. [12] transducing energy, [13] emitting light, [14] initiating self-healing, [15] acting as molecular magnets, [16] acting as redox flow batteries, [17] enabling next generation computing, [18] and superconducting.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly thereafter, a report from the US Food and Drug Administration (FDA) concluded that BIA 10‐2474 has a peculiar toxicity profile that does not extend to other FAAH inhibitors. In fact, an in‐depth reinvestigation uncovered a series of off‐target proteins for the same compound …”
Section: Introductionmentioning
confidence: 99%